2015
DOI: 10.1037/adb0000060
|View full text |Cite
|
Sign up to set email alerts
|

How do impulsivity traits influence problem gambling through gambling motives? The role of perceived gambling risk/benefits.

Abstract: 7Although substantial research suggests that motivations have been found to mediate the 8 relationships between impulsivity traits and various forms of substance use, no studies have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 68 publications
2
33
0
1
Order By: Relevance
“…Among the dimensions of impulsivity, positive urgency was positively related to both gambling frequency and problem gambling. The finding that positive urgency predicts greater gambling problems supports the findings of previous research (Canale et al, 2015a;Cyders & Smith, 2008;Fischer & Smith, 2008) which suggest that individual differences in problem gambling are directly associated with positive affect.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Among the dimensions of impulsivity, positive urgency was positively related to both gambling frequency and problem gambling. The finding that positive urgency predicts greater gambling problems supports the findings of previous research (Canale et al, 2015a;Cyders & Smith, 2008;Fischer & Smith, 2008) which suggest that individual differences in problem gambling are directly associated with positive affect.…”
Section: Discussionsupporting
confidence: 81%
“…Recent studies found that young people who tend to act rashly in response to extreme moods show higher enhancement and coping motives, which are, in turn, positively related to gambling problems (Canale, Vieno, Griffiths, Rubaltelli, & Santinello, 2015a). They were also more likely to have lower levels of deliberative decision-making and higher preferences for immediate/small rewards, which in turn were positively related to gambling problems (Canale, Vieno, Griffiths, Rubaltelli, & Santinello, 2015b).…”
Section: Introductionmentioning
confidence: 97%
“…Canale, Vieno, Griffiths, Rubaltelli, & Santinello, 2015;Liu et al, 2013) and reason for gambling (e.g., to better elucidate the differences between online and non-online gamblers.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, in comparison to neuroticism, negative urgency is a narrower construct that has been linked to specific executive and affective mechanisms (e.g. poor pre-potent response inhibition, heightened emotion reactivity) [7,8], allowing the development of more focused prevention and treatment strategies [9].…”
Section: The Benefits Of Using the Upps Model Of Impulsivity Rather Tmentioning
confidence: 99%